Hepatitis C Virus Infection Induces Inflammatory Cytokines and Chemokines Mediated by the Cross Talk between Hepatocytes and Stellate Cells - Nishitsuji, Hironori (American Society for Microbiology, 2013)
Inflammatory cytokines and chemokines play important roles in inflammation during viral infection. Hepatitis C virus (HCV) is a hepatotropic RNA virus that is closely associated with chronic liver inflammation, fibrosis, and hepatocellular carcinoma. During the progression of HCV-related diseases, hepatic stellate cells (HSCs) contribute to the inflammatory response triggered by HCV infection. However, the underlying molecular mechanisms that mediate HSC-induced chronic inflammation during HCV infection are not fully understood. By coculturing HSCs with HCV-infected hepatocytes in vitro, we found that HSCs stimulated HCV-infected hepatocytes, leading to the expression of proinflammatory cytokines and chemokines such as interleukin-6 (IL-6), IL-8, macrophage inflammatory protein 1α (MIP-1α), and MIP-1β. Moreover, we found that this effect was mediated by IL-1α, which was secreted by HSCs. HCV infection enhanced production of CCAAT/enhancer binding protein (C/EBP) β mRNA, and HSC-dependent IL-1α production contributed to the stimulation of C/EBPβ target cytokines and chemokines in HCV-infected hepatocytes. Consistent with this result, knockdown of mRNA for C/EBPβ in HCV-infected hepatocytes resulted in decreased production of cytokines and chemokines after the addition of HSC conditioned medium. Induction of cytokines and chemokines in hepatocytes by the HSC conditioned medium required a yet to be identified postentry event during productive HCV infection. The cross talk between HSCs and HCV-infected hepatocytes is a key feature of inflammation-mediated, HCV-related diseases.